Urgency of establishing responsive local regulations to realize good local governance - Rochmawanto, Munif; Suhartono, Slamet; Hufron, Hufron; Hadi, Syofyan (Technium Social Sciences Journal, 2022)
The formation of responsive regional regulations based on premise that Indonesia is a democratic legal state. A democratic rule of law is obligated to guarantee protection of human rights and provide justice through community participation in formation of regional regulations. As a good legal product, Regional Regulations must reflect shared values of justice, and be responsive to community needs. Regional Regulations are regional legal products established by Regional People’s Representative Council (DPRD) with the joint approval of Regional Head in context of carrying out regional autonomy and co-administration tasks. Regional autonomy the rights, powers and obligations of autonomous regions to regulate and manage their own government affairs and interests local community within system of Unitary State Republic of Indonesia. Thus the substance of Regional Regulation must be made in accordance with wishes and needs local community/region. The urgency of forming responsive regional regulations to realize regional governance is to realize justice and provide protection for human rights through community participation in formation of regional regulations. Realizing good Regional Regulations based on the principles of legality, "principles can be implemented" and "principles can be recognized" which are formal and material principles in formation of laws and regulations, and are formed in accordance with the interests of society.